2019
DOI: 10.1111/aas.13315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastric residual volume in fasting diabetic patients using gastric ultrasound

Abstract: The study was registered at clinicaltrials registry system with trial number: NCT 03438305. URL: https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S00 07SDV&selectaction=Edit&uid=U0002TST&ts=3&cx=ohgvvk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 22 publications
2
30
1
3
Order By: Relevance
“…Patient pathology, particularly concomitant diabetes, theoretically may contribute to increased risk of delayed gastric emptying. 130 In addition, this topic generally is unstudied in the setting of transesophageal echocardiography, which may contribute to the risk of aspiration. From a practical standpoint, cardiac surgical times can be unpredictable, and even elective schedules are dynamic, which may complicate the implementation of shorter NPO timelines.…”
Section: Continued Consumption Of Clear Liquids Until 2 Tomentioning
confidence: 99%
“…Patient pathology, particularly concomitant diabetes, theoretically may contribute to increased risk of delayed gastric emptying. 130 In addition, this topic generally is unstudied in the setting of transesophageal echocardiography, which may contribute to the risk of aspiration. From a practical standpoint, cardiac surgical times can be unpredictable, and even elective schedules are dynamic, which may complicate the implementation of shorter NPO timelines.…”
Section: Continued Consumption Of Clear Liquids Until 2 Tomentioning
confidence: 99%
“…Previous studies have reported the use of ultrasound imaging preoperatively for bedside assessment of gastric content and volume in non-fasting, diabetic, severely obese, and intensive care patients (8)(9)(10). Sayyadi et al (9).…”
Section: Introductionmentioning
confidence: 99%
“…Bouvet et al (2017) reported the prevalence of the full stomach in 56% of emergency surgery patients and suggested that preoperative ultrasound assessment of gastric contents may be particularly helpful in this case [4]. Sabry et al (2019) demonstrated that gastric ultrasound is used as a reliable method to assess the residual gastric volume in fasting diabetics compared to the healthy control for elective surgery and reported that the residual gastric volume in diabetic patients fasting for 8 hours was higher than in patients without diabetes scheduled for elective surgery [10].…”
Section: Resultsmentioning
confidence: 96%
“…Based on a study done by Sabry et al, [10] to show a difference in the incidence of change of aspiration risk after gastric ultrasonographic assessment in comparison to clinical assessment with a con dence interval at 95% and the acceptable margin of error at 5%. The p-value was considered signi cant if < 0.05 and needed minimally a sample size of 45 patients.…”
Section: Sample Size Calculationmentioning
confidence: 99%